Adenovirus Detection in Children Under 5 Years With Diarrheal Syndrome. State of Zulia, Venezuela - Ricardo Atencio; Jennifer Gotera; Suet Chan; Cristina Paredes; Angela Bracho; Daniel Marín; Rafael Villalobos; Sergio Osorio; María A Atencio; María A. V Atencio; Sandy García (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2015)
Diarrhea is one of the main causes of childhood illness worldwide, especially in developing countries, where diarrheal diseases represent a very important factor in infant mortality, reaching primarily, those under 5 years. It is estimated that adenoviruses can be the second causal agent for acute diarrhea after rotaviruses and that they contribute between 5 and 20% of the children hospitalized for diarrhea. The aim of this study was to detect the presence of enteric adenoviruses 40 and 41 using the PCR technique in diarrheal stool samples of 190 children of both sexes under 5 years old. Different municipalities and health centres in Zulia collected samples from January, 2011, to November, 2013. The study found 22.10% (42/190) positive reactions in the samples studied, demonstrating that this virus causes a great part of the diarrheal cases in children. According to source, the highest number of cases was in the Jesus Enrique Lossada municipality with 28.57%. Adenovirus dominated the nursing infant group with 52.38% (22/127), showing significant differences (p<0.05) when compared to other age groups. Males were the most affected with 57.14% (24/92) compared to females. The ratio in terms of virus positivity and clinical manifestations evidenced diarrhea in 42/42 (100%), followed by vomiting 28/42 (73.80%). The present study indicates that adenoviruses 40 and 41 are important etiological agents for diarrhea in the child population studied.